The Role of Motivation and Environmental Synergy on Improving the Quality of Qur'an Memorization at Ngalah Islamic Boarding School: Case Study of Tahfidz Dormitory Program H - Isyatil Fitri; Ali Muhtarom; Moh. Nur Hadi (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the role of motivation and environmental synergy in improving the quality of memorization of the Qur'an in the Dormitory H Tahfidz Program. The focus of the research highlights the challenges faced in memorizing the Qur'an, ranging from solid time management, heterogeneity of santri backgrounds, to the limitations of varied learning methods. To overcome these obstacles, this study emphasizes the importance of motivational factors-both intrinsic and extrinsic-as well as environmental support which includes intensive guidance, periodic evaluation, and provision of conducive learning facilities. The research method used was a qualitative approach with a case study, which involved three data collection techniques: participatory observation for three months, in-depth interviews, and documentation studies related to activity schedules, achievement records, and memorization guidelines. Data were analyzed thematically to identify patterns of motivation, environmental synergy, and improved memorization quality. The results showed that intrinsic motivation, rooted in sincerity and spiritual awareness to get closer to Allah, played a major role in fostering strong intentions in memorization. Meanwhile, extrinsic motivation that comes from family encouragement, appreciation, and supervisor support also boosts the enthusiasm of students. The synergy of the environment, which includes personal guidance, group learning, application of the reward and punishment system, and a structured and comfortable physical environment, is proven to support the learning process significantly. The implications of this study confirm the need for a holistic approach in the Tahfidz program, where strengthening motivation and optimizing the learning environment must go hand in hand to achieve optimal memorization results. The findings are expected to be used as a reference for other pesantren in designing strategies to improve the quality of memorization of the Qur'an as well as developing a more adaptive and supportive learning system.